Reframing developmental psychology : perspectives from the Global South - Tuli, Mila; Chaudhary, Nandita (Perspectives on human development., 2025)
Reframing Developmental Psychology: Perspectives from the Global South critically examines the dominant frameworks in Developmental Psychology, challenging the discipline's reliance on mainstream theories, universalist assumptions, and culturally narrow research samples. By addressing issues such as WEIRD (Western, Educated, Industrialized, Rich, Democratic) psychology and developmentalism, the book calls for a more inclusive and culturally grounded approach to understanding human development. Contributors to this volume carefully question the assumptions that underlie conventional developmental discourse and advocate acknowledging historical contexts, cultural specificity, and diverse epistemologies, while retaining the larger objective of universal scientific study. Universalism should not imply uniformity. Emphasizing perspectives from the Global South - understood as both a geographical and conceptual space - this book highlights the importance of integrating indigenous knowledge systems, alternative methodologies, and collaborative scholarship in the advancement of a culturally informed study of human developmental processes. It critiques the over-reliance on positivist, standardized research methods that fail to capture the complexities of meaning-making and cultural variation. Instead, it calls for a redefinition of what constitutes valid knowledge, advocating for interdisciplinary approaches that bridge psychology, anthropology, sociology, literature and philosophy. By dismantling colonial legacies and reconsidering the ethical, epistemological, and methodological foundations of the field, the book fosters a vision of Developmental Psychology that is equitable, pluralistic, and responsive to the diverse realities of human experience.